Analysis of Factors Causing High Unemployment Rates in North Sumatra Due to the Covid-19 Pandemic - Lubis, Atika Atayarisah; Saputra, Firman; Lubis, Regita; Saragi, Sarah Lylia (Lembaga Riset Mutiara Akbar (LARISMA), 2023)
The Covid-19 pandemic that was present in Indonesia resulted in a large number of deaths and transmission of the Covid-19 Virus. In this regard, the government issued various policies such as Physical Distancing, Large-Scale Social Restrictions (PSBB), and Restrictions on Community Activities (PPKM). This policy is considered quite significant in breaking the chain of the spread of the Coronavirus, but this policyactually hits the economic sector where it causes an increase in the unemployment rate.Therefore, this study aims to determine what factors cause high unemployment in North Sumatra. The research method carried out by researchers is Literature Review by reviewing various articles from previous studies that have been published nationally in accredited scientific journals. In this study the authors used a data collection method, namely Literary Study where research was conducted by quoting several literature from books, articles, and other essays that are closely related to the factors causing the high unemployment rate in North Sumatra 2021 due to the Covid-19 Pandemic.The results of this study indicate that there are several factors causing the high unemployment rate . Among them are mass termination of employment relations, government policies such as PSBB and PPKM, and closure of employment opportunities